IMPLEMENTASI PENILAIAN PORTOFOLIO PADA PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR KARAKTER AL-ADZKIYA CIANJUR - Attorsusi, Sigit Moch; Mahpudin, Muhamad; Ahmad, Jajang; Mutaqin, Dadang Zenal (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This study aims to explore the implementation of portfolio assessment. The results showed that the learning outcomes of students in class VI A who used the portfolio assessment method were higher than the learning outcomes of students in class VI B who used the traditional assessment method. This can be seen from the average value of student learning outcomes in class VI A of 75.00 while the average value of student learning outcomes in class VI B of 65.00. Portfolio assessment can help teachers to measure students' learning progress comprehensively, covering cognitive, affective and psychomotor aspects. In addition, portfolio assessment can also provide opportunities for students to show their abilities to the fullest and motivate students to study harder. However, in its implementation, portfolio assessment at SDS Karakter Al-Adzkiya is still not optimal, especially in terms of teachers' understanding of portfolio assessment, the availability of supporting facilities and infrastructure, and student motivation in collecting portfolios. Based on the results of this study, it is suggested to teachers and schools to apply portfolio assessment method in learning Islamic education, by improving teachers' understanding of the concepts, principles, and procedures of portfolio assessment, providing adequate facilities and infrastructure to support portfolio assessment, and increasing students' motivation to collect portfolios